Chloride, Sodium and Calcium Intake Are Associated with Mortality and Follow-Up Kidney Function in Critically Ill Patients Receiving Continuous Veno-Venous Hemodialysis-A Retrospective Study - Hellman Tapio; Uusalo Panu; Järvisalo Mikko J (MDPI, 2025)
Background: Studies on the association between solute, nutrition and fluid intakes and mortality and later kidney function in critically ill acute kidney injury (AKI) patients receiving continuous veno-venous hemodialysis (CVVHD) are scarce.
Methods: Altogether, 471 consecutive critically ill AKI patients receiving CVVHD in the research intensive care unit (ICU) were recruited in this single-center, retrospective study.
Results: The median age was 66 (58-74) years, and 138 (29.3%) were female. The 90-day and one-year mortalities were 221 (46.9%) and 251 (53.3%), respectively. After adjusting for age, sex, Acute Physiology and Chronic Health Evaluation II (APACHE) score, coronary artery disease, immunosuppression, ICU care duration, mechanical ventilation requirement, vasopressor requirement and study time period, the cumulative daily intake of potassium, chloride, sodium, phosphate, calcium, glucose, lipids and water was associated with one-year mortality in separate multivariable cox proportional hazards models. In a sensitivity analysis excluding patients who died within the first three days of ICU care, the daily intake of chloride (hazard ratio (HR) 1.001, confidence interval (CI) 95% 1.000-1.003, p = 0.032), sodium (HR 1.001, CI 95% 1.000-1.002, p = 0.031) and calcium (HR 1.129, CI 95% 1.025-1.243, p = 0.014) remained independently associated with mortality within one-year in the respective, similarly adjusted multivariable cox analyses. The cumulative daily intake of chloride, sodium, calcium and water was independently associated with the estimated glomerular filtration rate (eGFR) at 90 days follow-up in separate substantially adjusted multivariable cox proportional hazards models.
Conclusion: The cumulative daily intake of chloride, sodium and calcium is associated with mortality and daily chloride, sodium, calcium and water intake is associated with follow-up eGFR in critically ill patients with CVVHD-treated AKI.